Peramalan jumlah produksi tanaman kelapa sawit dengan menggunakan metode arima (autoregressive integrated moving average) - Elvani, Sendy Parlinsa; Utary, Anis Rachma; Yudaruddin, Rizky (JURNAL MANAJEMEN, 2016)
This research aims to apply ARIMA method in predicting and estimating the amount of palm oil crop production for the next period. This research object is the amount of palm oil crop productionin the form of bunches whereas the data used is the historical data from the amount of palm oil crop production on January 2013 to December 2015.The results from this research showed that there are some models which can be used to predict, ARIMA (3,1,3), ARIMA (3,1,1), ARIMA (3,1,2), ARIMA (2,1,3). From the fourth model, ARIMA (3,1,1) model is the best model and the most feasible model to forecast with the smallest value of AIC and SIC. The forecasting results increased from the previous period. The forecasting result for 2016 amounted 25.905,506 tonnes and for 2017 amounted 33.260,761 tonnes.Keyword: Forecasting, Palm Oil Production, ARIMA.